Comparative Study of Inguinal Hernia Repair under Local Anesthesia versus Spinal Anesthesia in Reducing Hospital Stay of Patient - Kafeel, Urwah; Aslam, Madiha; Butt, Muhammad Sulman; Sufyan , Muhammad; Saad, Mohammad; Khalid, Hafsa (Indus Journal of Bioscience Research, 2025)
Background: Inguinal hernia is a very common problem in men. Mostly end in hernia repair. As inguinal hernia present in lower abdomen, below umbilicus, repair can be done under spinal anesthesia. Local anesthesia can also be a good replacement for spinal anesthesia. But local evidence is scarce and need to conduct a trial to find more effective and beneficial mode of anesthesia in inguinal hernia repair. Objective: To compare and evaluate the outcomes of inguinal hernia repair under local anesthesia versus spinal anesthesia in reducing inpatient stay. Study Design: Randomized controlled trial. Place and Duration: Surgery Department, Lahore General Hospital, Lahore from September 2022 to March 2023. Material and Methods: There were 40 people undergoing inguinal hernia repair who were enrolled. Consent was obtained, and demographics were noted. Patients were randomly segregated into two groups. In Group A , repair was done under local anesthesia, while in Group B, repair was done under spinal anesthesia. Outcomes were noted and analyzed using SPSS version 25. Results: In patients of local anesthesia, mean age was 47.20 ± 17.95 years. In Spinal anesthesia group, mean age of patients was 53.60 ± 13.09 years. The mean duration of hernia was 2.20 ± 1.61 years vs. 2.65 ± 1.73 years, respectively. The mean pain score on day 1 of surgery was 1.85 ± 0.88 with local anesthesia and 4.00 ± 0.79 with spinal anesthesia (p<0.001). Hematoma formed in 8 (40%) cases and seroma in 6 (30%) cases in spinal anesthesia group while zero in local anesthesia group. Urinary retention occurred in 3 (15%) vs. 12 (60%) cases (p<0.05). The mean time taken to start walking was 1.00 ± 0.00 days with local anesthesia vs. 1.55 ± 0.51 days with spinal anesthesia, started using stairs after 2.30 ± 0.47 days vs. 3.20 ± 1.01 days, mean time to return to work was 4.75 ± 0.91 days vs. 6.65 ± 1.18 days (p<0.05). Conclusions: The outcomes of local anesthesia are better than spinal anesthesia for inguinal hernia repair.